Boosting of SARS-CoV-2 immunity in nonhuman primates using an oral rhabdoviral vaccine. Issue 15 (1st April 2022) - Peng, Kah-Whye; Carey, Timothy; Lech, Patrycja; Vandergaast, Rianna; Muñoz-Alía, Miguel Á.; Packiriswamy, Nandakumar; Gnanadurai, Clement; Krotova, Karina; Tesfay, Mulu; Ziegler, Christopher; Haselton, Michelle; Sevola, Kara; et al.
Abstract: An orally active vaccine capable of boosting SARS-CoV-2 immune responses in previously infected or vaccinated individuals would help efforts to achieve and sustain herd immunity. Unlike mRNA-loaded lipid nanoparticles and recombinant replication-defective adenoviruses, replicating vesicular stomatitis viruses with SARS-CoV-2 spike glycoproteins (VSV-SARS2) were poorly immunogenic after intramuscular administration in clinical trials. Here, by G protein trans-complementation, we generated VSV-SARS2(+G) virions with expanded target cell tropism. Compared to parental VSV-SARS2, G-supplemented viruses were orally active in virus-naive and vaccine-primed cynomolgus macaques, powerfully boosting SARS-CoV-2 neutralizing antibody titers. Clinical testing of this oral VSV-SARS2(+G) vaccine is planned.